Monitoring Low-Cycle Fatigue Material-Degradation by Ultrasonic Methods - R. Himawan; H. Katoh; A. Cahyono (PPIKSN-BATAN, 2010)
Any system consisting of structural material often undergoes fatigue, which is caused by dynamic load cycle. As a structural system, nuclear power plant is very likely to have low-cycle fatigue at many of its components. Taking into account the importance of monitoring low-cycle fatigue on structural components to prevent them from getting failure, the authors have conducted a work to monitor material degradation caused by low-cycle fatigue by using ultrasonic method. An alloy of Cu-40Zn was used as a test specimen. Ultrasonic water immersion procedure was employed in this ultrasonic test. The probe used is a focusing type and has frequency as high as 15 MHz. The specimen area tested is in the middle part divided into 14 points × 23 points. The results, which were frequency spectrums, were analyzed using two parameters: frequency spectrum peak intensity and attenuation function gradient. The analysis indicates that peak intensity increases at the beginning of load cycle and then decreases. Meanwhile, gradient of attenuation function is lower at the beginning of fatigue process, and then consistently gets higher. It concludes that low-fatigue material degradation can be monitored by using ultrasonic method.Received: 20 November 2009; Revised: 31 August 2010; Accepted: 31 August 2010